Acute and chronic toxicity of aqueous extract of Ruta montana L. in rodents - Merghem, Mounira; Dahamna, Saliha; Rezzagui, Abir; Boussahel, Soulef; Belguet, Assia; Dehimi, Khadidja; Harzallah, Daoud (Pharmacognosy Communications)
The objective of this study was to evaluate the acute and chronic toxicity of aqueous extract of Ruta montana L. in mice and rats. For the acute study, aqueous extract of Ruta montana L. was administered to mice in single doses of 0–12 g/kg given by gavage. General behavior, adverse effects and mortality were determined for up to 14 days. In the chronic study, the extract was administered orally at doses of 0, 100, 300 and 600 mg/kg daily for 90 days to rats. Biochemical and hematological parameters were determined after 30 and 90 days. Enzyme activities were assayed in the plasma samples obtained. AST (GOT), ALT (GPT), cholesterol, triglyceride and glucose. The results showed a decrease in RBC and WBC after one month (sub chronic dose) of treatment (in males 75.48% and 51.47% respectively). However, an increase was registered after 3 months (in males 130% and 171% respectively). This is probably explained by the effect of this plant extract on the erythropoiesis. A decline was observed on plasma enzyme activities in both GOT and GPT on males after one month by 51.67% and 68.6% respectively. A decrease was noticed in both cholesterol and triglyceride levels. Urine analysis was negative for glucose, bilirubin, ketones, proteins, nitrite and leukocytes in the control and treatment groups. There were no significant differences in the body and organ weights between controls and treated animals of both sexes. The histopathological studies have been showed vascular congestion and lesions of interstitial nephrite.
Keywords: Acute toxicity; Biochemical parameters; Chronic toxicity; Hematological parameters; Ruta montana L.; Mountain rue